A Survey Paper on Securing Cloud Computing using ABS Signatures - Timande, Shruti; Dhabliya, Dharmesh (International Journal of Psychosocial Rehabilitation, 2025)
In the realm of specialized life, distributed computing has ended up as a basic part; furthermore, understanding the method for business is changing and is prone to keep changing into what’s to come. Utilizing distributed storage administrations implies that you and others can get to and offer documents over a scope of gadgets and positions. Records, for example, photographs and recordings, can once in a while be unmanageable to email in the event that they are too enormous or you have a portion of information. You can transfer your information to a distributed storage supplier, which implies you can rapidly flow your information with the assistance of cloud administration, and you can impart your information documents to anybody you pick. Since distributed computing shares disseminated assets by means of a system in the open environment along these lines, it makes it less secure. Information security has turned into a noteworthy issue in information sharing on the cloud. The fundamental witticism behind our framework is that it secures the information and produces the key for every exchange so every client can secure our common information from the outsider, i.e., the untrustworthy programmer